Unraveling urban food availability dynamics and associated social inequalities: Towards a sustainable food environment in a developing context. (February 2022) - Wang, Lingqi; He, Shenjing; Zhao, Chong; Su, Shiliang; Weng, Min; Li, Guie
Highlights: Conceptual framework which illustrates a ternary perception of urban food availability is proposed. A set of indicators are developed to capture the food availability dynamics in a typical Chinese metropolitan. Social inequalities in food availability over time are unpacked using multilevel regression. New knowledge is gained regarding urban food availability dynamics and associated social inequalities. Abstract: The essential role of food environment in achieving urban sustainability has been widely recognized worldwide. A myriad of studies has emphasized food availability as the basic starting point for a comprehensive understanding of urban food environment. However, most of the empirical evidences were based on Western cases, and how urban food availability and associated social inequalities change over time remains poorly understood for the developing world. This paper first establishes a conceptual framework which illustrates a ternary perception of urban food availability and explains why accessibility, diversity and locational association should be considered as a whole package. Guided by the framework, a set of indicators are developed and further applied to capture the food availability dynamics from 2016 to 2018 within Hangzhou metropolitan in China. Last, multilevel regression is applied to unpack the social inequalities in food availability over time. Results show that overall temporal changes of food availability are not obvious but the spatial heterogeneity is prominent and lasting. Particularly, food environment is rather more complex in the central area but is much healthier compared with the outskirts. Significant social equalities in food availability persist but present a declining trend within the research period. More specifically, food availability is subjected to socioeconomic status (SES) at both community level and sub-district level. Such results go beyond prior findings through highlighting a nested effect of multilevel neighborhood SES on urban food availability. Several possible avenues for creating sustainable food environment within metropolitan areas in a developing context are discussed based on the main findings. The discovered urban food availability dynamics and associated social inequalities differ a lot with those reported in Western cities. This paper is thus believed to throw fresh light on urban sustainable food environment research in non-western context.